Genome-wide mapping of transcriptional enhancer candidates using DNA and chromatin features in maize - Oka, Rurika; Zicola, Johan; Weber, Blaise; Anderson, Sarah N.; Hodgman, Charlie; Gent, Jonathan I.; Wesselink, Jan-Jaap; Springer, Nathan M.; Hoefsloot, Hubb C.J.; Turck, Franziska; Stam, Maike (BioMed Central, 2017)
Background